Biodegradability Assessment of Aquaculture Effluents: A Comprehensive Analysis of BOD and COD Using Multivariate Statistical Techniques - Savaliya, B. D.; Solomon, Jebarson; Karale, Tejaswini; Kumar, Ganesh; Paul, Tapas; Kumar, Saurav; Bhusare, Saiprasad; Priyadharshini, Thangaraj; Renuka (International Journal of Bio-resource and Stress Management, 2026)
The study was conducted during January, 2023 to December, 2024 at Tirunelveli, Tuticorin and Kanyakumari district of Tamil Nadu, India to investigate the biodegradability of effluents collected from semi-intensive aquaculture systems operating in Tamil Nadu based on biodegradability index calculated from Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD). BOD indicated the oxygen needed to biologically degrade organic matter; COD measured both biodegradable and nonbiodegradable organic matter. The BOD/COD ratio (Biodegradability index) averaged 0.46, showing that the wastewater exhibited moderate biodegradability, implying that biological treatment was feasible but microbial seeding might enhance efficiency. Seasonal peaks in May correlated with increased feed input and organic waste accumulation; lower values in October and November reflected reduced production. Regression analysis identified a quadratic polynomial as the best predictor of BOD from COD, underscoring the value of mathematical models for monitoring wastewater quality. This study demonstrated that integrating BOD and COD data with statistical tools could improve effluent management. Expanding sustainable aquaculture would require implementing treatment technologies suited to effluents with moderate biodegradability. The findings provided baseline information for designing effluent treatment plants, optimizing microbial consortia and informing policy on discharge standards.